Long-Term Stable 1-butyl-3-methylimidazolium Hexafluorophosphate/Ag Metal Composite Membranes for Facilitated Olefin Transport - Kang, Sang Wook (Membranes (Basel), 2020)
For the preparation of long-term stable ionic liquid/Ag nanoparticles composites, we compared the separation performance of 1-butyl-3-methylimidazolium tetrafluoroborate (BMIM(+)BF(4)(−))/Ag, and 1-butyl-3-methylimidazolium hexafluorophosphate (BMIM(+)PF(6)(−))/Ag composite membranes with time. Separation performance showed that the BMIM(+)PF(6)(−)/Ag metal composite membrane was more stable than the BMIM(+)BF(4)(−)/Ag metal composite membrane for more than 160 h. These differences in long-term stability in BMIM(+)PF(6)(−)/Ag and BMIM(+)BF(4)(−)/Ag metal composite membranes was attributable to the phase separation between ionic liquid and nanoparticles. In particular, the phase separation between ionic liquid and silver nanoparticles was not observed with time in hydrophobic ionic liquid BMIM(+)PF(6)(−), confirmed by X-ray photoelectron spectroscopy.